Cellular prion protein-mediated protection against influenza A virus infection. (January 2019) - Chida, Junji; Sakaguchi, Suehiro
The cellular prion protein, termed PrP C, is a glycoprotein abundantly expressed in brains and to a lesser extent in non-neuronal tissues including lungs. It was reported that PrP C is expressed by lung epithelial cells in mice, and that it may play a protective role against lethal infection with influenza A viruses (IAVs). This may occur by regulating Cu content and superoxide dismutase (SOD) activity, eventually reducing oxidative stress in infected lungs. Antioxidative therapeutics have been demonstrated to protect mice from lethal infection with IAVs. Therefore, PrP C might be a new target molecule for development of IAV therapeutics. Here, we introduce the antiviral mechanism of PrP C against IAV infection and discuss perspectives of PrP C -targeting therapeutics against IAV infection.